Association between serum transthyretin and intracranial atherosclerosis in patients with acute ischemic stroke - He, Jinfeng; Zhu, Jiamin; Zhang, Wenyuan; Zhan, Zhenxiang; Fu, Fangwang; Bao, Qiongqiong (Frontiers in Neurology, 2022)
Background Intracranial atherosclerotic stenosis (ICAS) is a primary cause of ischemic stroke. In addition to dyslipidemia, inflammation has been recognized as a potential pathogenesis of atherosclerosis. It remains unknown whether there is a link between transthyretin and ICAS as an inflammatory index. Methods Consecutive patients with acute ischemic stroke admitted to the Second Affiliated Hospital of Wenzhou Medical University between January 2019 and June 2020 were retrospectively analyzed. Blood samples were collected from all patients within 24 h of admission to detect their serum transthyretin levels. ICAS was defined as at least one intracranial artery stenosis on vascular examination with a degree of stenosis ≥50%. Multivariable logistic regression analysis was used to identify independent factors associated with ICAS. Restricted cubic spline models were used to depict patterns in the association between serum transthyretin levels and ICAS. Results In total, 637 patients with acute ischemic stroke were included in this study, of whom 267 (41.9%) had ICAS. Compared with the patients without ICAS, serum transthyretin levels in patients with ICAS were significantly lower (226.3 ± 56.5 vs. 251.0 ± 54.9 mg/L; p < 0.001). After adjusting for potential confounders, patients in the lowest tertile showed a significant increase in ICAS compared to those in the highest tertile (odds ratio, 1.85; 95% confidence interval, 1.12–3.05; p = 0.016). This negative linear association is also observed in the restricted cubic spline model. However, this association may only be observed in men. Age, National Institutes of Health Stroke Scale score, hemoglobin A1c level, and low-density lipoprotein cholesterol level were independently associated with ICAS. Conclusions Decreased serum transthyretin levels are associated with a more severe ICAS burden in patients with acute ischemic stroke. Our findings suggest that transthyretin may play a role in the pathogenesis of ICAS and provide insight into the control of inflammation for the treatment of ICAS.